Surgical Outcomes and Associated Morbidity of Active and Expectant Management of Second-Trimester Placenta Accreta Spectrum (PAS) - Jessian L. Munoz; Rachel Counts; Amanda E. Lacue; Kayla E. Ireland; Patrick S. Ramsey; Kristyn Brandi (Medicina)
Background and Objectives: Management of second-trimester placenta accreta spectrum (PAS) is currently center-dependent with minimal evidence-based practices. This study aims to analyze outcomes of hysterectomy as second-trimester active management (AM) versus cesarean hysterectomy as expectant management (EM) in cases of PAS with intraoperative and postoperative outcomes. Materials and Methods: This study is a retrospective case-control study of patients with a pathology-confirmed diagnosis of PAS managed at a single center over 16 years (2005–2020). All cases were diagnosed during the first or second trimester by ultrasonography and managed by the same multidisciplinary team with delivery within the second trimester. Results: Thirty-four patients with PAS were diagnosed and delivered by the second trimester. Of these, (41.1%) elected for active management and 20 (58.9%) for expectant management but ultimately required delivery prior to 28 weeks’ gestation. Baseline demographics were similar between groups. Intraoperatively, no differences were noted in operative time (191.5 vs. 203 min, p = 0.85), blood loss (2300 vs. 2600 cc, p = 0.85), or incidental cystotomy (1 vs. 7, p = 0.10). Postoperative length of stay was similar (3 vs. 3.5 days, p = 0.28), and ICU admission was not statistically different (6 vs. 12, p = 0.48). Conclusions: This retrospective study suggests that when hysterectomy is planned, there is no difference in maternal outcomes and morbidity with an expectant management with cesarean hysterectomy in the second trimester compared to proactive cesarean hysterectomy.